Assessment of dicranopteris linearis, nephrolephis bifurcata, stenochlaena palustris and acrostichum aureum heavy metal sequestration rate stability at highly weathered soil area - Mohd Latiff, Nur Hanie; Othman, Rashidi; Hj. Baharuddin, Zainul Mukrim (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Phytoremediation in plant system functions to degrade, extract or inactivate potentially hazardous compounds in contaminated soil, air or water. Phytoremediation involves different mechanisms such as phytodegradation, rhizodegradation, phytoextraction or phytostabilisation. Therefore, this study aimed to assess four terrestrial fern species to sequester heavy metal contaminants from laterite soil. Samples were taken from 3 different localities in Perak, Selangor and Johor to investigate their heavy metal sequestration rate stability and pattern distribution in this highly weathered soil. 10 heavy metals were measured using ICP-MS (Perkin Elmer NexION 300X). Al and Fe were detected with a high concentration at most of the sites with different volume of concentration. The analysis of variance (ANOVA) established highly significant differences (P<0.0001) for all species of ferns and all interactions. Since there are many factors that contribute to the heavy metal accumulation, plant species can be one of the alternative measures to remediate soil heavy metal contaminants. Thus, this green technology can be a relatively cheap treatment for other heavy metal contamination sites such as landfill area.